A autonomia decisória das empresas transnacionais: os desafios e perspectivas sobre a proteção dos direitos humanos - Soares, Michael Lindemberg Barros (2020)
Transnational companies play an essential role in the development and economy of a state. The fact that they act beyond state borders gives them the character of companies without nationality. This trait is an effect not only of the expansion of the world market - more and more prone to the free circulation of products, technologies, investments, financial flows - but also of the direct or indirect action of States and the participation of Private Agents. However, from a legal perspective, below and beyond borders, the opening of these interstate spaces has caused concern: what are the limits for the performance of these companies, since they are equipped with the ability to move resources on a global scale? In seeking to resolve this problem, States with an interest in setting up these companies in their territories, aware of the economic strength of these organizations, try to restrict their freedom through regulatory mechanisms. However, there is still another concern: is the modus operandi of these companies in line with the deliberations about human rights? However, such an impasse led the UN itself to establish guiding principles for the performance of these companies (even if in a non-binding manner), with the purpose of protecting and respecting human rights, as well as repairing any violations of such rights. It is in this context that the present research is located, whose aim is, through the hypothetical-deductive method and historical-normative analysis, to propose an effective way for transnational companies to operate in interstate spaces, which must cover both respect for sovereignty political-economic status of states regarding human preservation globally.